Semiotika Visual Logo Brand Arsitektur Layanan Lembaga Amil Zakat Dompet Amanah Umat Sidoarjo - Aliv Fatima Latifah; Aris Sutejo (Student Research Journal, 2023)
In this study, the logos of the services of the Lembaga Amil Zakat Dompet Amanah Umat (LAZDAU) were analyzed using the semiotic theory by Roland Barthes. Through this analysis, the study shows how visual elements in the logo such as color, shape, and typography, interact to form meaning. The results of the analysis show that these logos not only function as the identity of the institution, but also as an effective visual communication tool. These logos communicate the mission, vision, and values of the institution to the public. This study also shows how a logo can influence public perception of a program or service provided by an institution. In addition to showing the importance of logo design in visual communication, this study provides new insights into how semiotics can be used to understand and analyze the logo of the service that Lembaga Amil Zakat Dompet Amanah Umat (LAZDAU) provides.